A new Hedysarum L. species (Fabaceae) from Türkiye, Hedysarum dazkiriense - Aytaç Zeki̇; Ertuğrul, Tuğba; Erst, Andrey; Fi̇şne Ahter (Phytotaxa, 2022)
A new species, Hedysarum dazkiriense, in the genus Hedysarum (Fabaceae) was described and illustrated here and is only known from Dazkırı district in Afyonkarahisar Province in Türkiye. The species belongs to sect. Multicaulia and it is closely related to H. syriacum, but it is distinguished from it by having 5–8 pairs and smaller leaflets (3–7 × 1–2 mm, not 4–6 pairs and 15–22 × 5–12 mm); calyx 2–3 mm long (not 8–9 mm), standard 14–16 mm long (not 18–22 (–24) mm). Also, it is similar to H. pestalozzae, but distinctly different from it by having smaller leaflets (3–7 × 1–2 mm, not 5–14 × 2.5–4 mm), smaller calyx (2–3 mm long not 4–6 mm), lomentum sparsely hirsute and without setae (not densely tomentose, with or without setae). Taxonomic descriptions, images, the identification key, phenology, palinology and the IUCN threat category of the new species were presented. In addition, the geographical distribution of H. dazkiriense, H. syriacum and H. pestalozzae were mapped.